105 - RECOMMENDATIONS TO THE CAREGIVER OF THE CHILD WITH CONGENITAL LUXATION OF THE HIP: REPORT OF TWO CASE HISTORIES (Fiep Bulletin - online, 2011)
The Congenital Luxation of the hip is characterized by the loss of contact of the head of the femur acetabulum, incidence of the feminine sex (8:1), most commonly the unilateral form. If treated vigorously, it prevents complications that can compromise the prognosis. This work has as the objective to emphasize the importance of the physical therapist in the orientation to the caretaker, providing fast and accurate guidance and insurance. This study describes the case history of two subjects, describing the evolution of LCQ in two female children, where, in the first one, the pathology was diagnosed in the neonatal examination, and in the second, at six months of age. The resources used in the treatment had been Pavlik harnesses, immobilization of the pelvis-pedal type, plaster podálico lame person-femoral and cast of Atlanta. One can conclude that the based physiotherapeutic accompaniment in the used behaviors, added to the orientations of the caretaker, adds great value in the pathological processes of LCQ, how much to the optimum prognosis, and better quality of development to adult life, as well as preventing a surgical intervention for the dislocation correction. Based on these case histories, the accomplishment of new studies is proposed that aim at the physiotherapeutic intervention in the congenital dislocation of the hip and the necessary orientations for the families and/or caretakers.
Keywords: Congenital Luxation of the Hip; Displasia